Impact of surgery in patients with multiple sclerosis: a nationwide cohort study - Larsson, Emma; Iacobaeus, Ellen; von Oelreich, Erik; Eriksson, Jesper; Kåhlin, Jessica (Frontiers in Neurology, 2025)
BackgroundSurgery is a common exposure. Multiple sclerosis (MS) is a chronic neuroinflammatory demyelinating disease of the central nervous system and a systemic inflammatory activation caused by surgery may result in exacerbation of the disease. It is unknown how surgical procedures affect morbidity and mortality rates in MS.ObjectivesThis study aimed to investigate morbidity associated with surgical interventions in MS patients by assessing disease burden before and after surgery. Non-MS patients were used as controls, allowing for comparisons of disease burden and mortality between the two groups.MethodsThe cohort study analyzed data from the Swedish Perioperative Register, including 3,022 MS patients among over 1.5 million surgeries performed between January 2019 and March 2023. Disease burden was measured as the number of pre-specified ICD-codes before and after surgery.ResultsWe demonstrated that MS patients exhibited a higher mean number of diagnoses before and after surgery compared to controls. Specifically, the number of diagnoses peaked in the first month post-surgery but returned to baseline within three to 4 months. Notably, there were no significant differences in 30-day or 365-day mortality rates between MS and non-MS patients, highlighting the relative safety of surgical interventions for persons with MS.ConclusionThe findings suggest that surgery is generally safe for patients with MS, indicating that MS should not preclude necessary surgical interventions. Nevertheless, tailored preoperative assessments and postoperative care strategies are essential to address the unique health challenges encountered by MS patients, ensuring optimal surgical outcomes and monitoring for potential complications.